2007
DOI: 10.1128/aem.01478-07
|View full text |Cite
|
Sign up to set email alerts
|

Identification of opdA , a Gene Involved in Biodegradation of the Endocrine Disrupter Octylphenol

Abstract: Octylphenol (OP) is an estrogenic detergent breakdown product. Structurally similar nonylphenols are transformed via type II ispo substitution, resulting in the production of hydroquinone and removal of the branched side chain. Nothing is known, however, about the gene(s) encoding this activity. We report here on our efforts to clone the gene(s) encoding OP degradation activity from Sphingomonas sp. strain PWE1, which we isolated for its ability to grow on OP. A fosmid library of PWE1 DNA yielded a single clon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(33 citation statements)
references
References 38 publications
0
33
0
Order By: Relevance
“…An additional spike of NP mix (0.2 mM) did not support further growth. Such low growth on NP or OP has been observed in the degradation by other degraders (Porter & Hay, 2007;Tanghe et al, 1999). This might be caused by the toxicity of the metabolites from NP mix .…”
Section: Resultsmentioning
confidence: 72%
See 2 more Smart Citations
“…An additional spike of NP mix (0.2 mM) did not support further growth. Such low growth on NP or OP has been observed in the degradation by other degraders (Porter & Hay, 2007;Tanghe et al, 1999). This might be caused by the toxicity of the metabolites from NP mix .…”
Section: Resultsmentioning
confidence: 72%
“…PWE1 (opdA PWE1 gene product, EU002557). Porter & Hay (2007) reported that a recombinant E. coli strain harbouring opdA PWE1 was able to degrade an OP isomer, 4-(29,49,49-trimethylpentyl)phenol. More recently, Porter et al (2012) successfully cloned an opdA homologue (opdA Bayram and opdA TTNP3 ) from NP-degrading strains Bayram and TTNP3, respectively.…”
Section: Takeo and Othersmentioning
confidence: 99%
See 1 more Smart Citation
“…BR1, PR1 cell-free extracts did not show significant degrading activity, irrespective of NADH presence, suggesting that different co-factors may be involved on SMX breakdown in these organisms. The hydroxylation of substituted aromatic com-pounds can be promoted by different catalysts, such as flavoprotein monooxygenases [33,34] or cytochromes P450 [35]. Therefore, further studies are needed to elucidate if the catalysts involved on sulfonamide degradation by strains PR1 and BR1 belong to one of these protein families.…”
Section: Discussionmentioning
confidence: 99%
“…Flavoprotein monooxygenases (33,34) and cytochromes P450 (25) are known to catalyze electrophilic hydroxylations of substituted aromatic compounds, whereby hydroperoxo-flavin (35) and hydroperoxo-iron (44) species, respectively, act as the donor of electrophilic oxygen. It remains to be elucidated whether the hydroxylation activity of the Microbacterium sp.…”
Section: Discussionmentioning
confidence: 99%